School Funding and Student Achievement : Lessons Learned from Kentucky and Tennessee - Spears, Andy (SpringerBriefs in Political Science, 2015)
This Brief explores school funding reform in the states of Kentucky and Tennessee. In 1990, Kentucky passed the Kentucky Education Reform Act designed to overhaul that state's education system. Two years later, Tennessee passed the Education Improvement Act which included the Basic Education Plan, designed to foster equity in funding among the state's schools. Initiated as a result of lawsuits against the states' educational systems, both programs dealt with school funding, specifically funding equalization among districts. This Brief examines the environments that precipitated funding reform in each state as well as the outcomes of the reforms on student achievement. The similarities and differences between the approaches in each state are analyzed and compared to related reform programs in other states. An in-depth study of regional educational reform in the United States, this Brief is of use to public policy scholars as well as education policy consultants and other school system or state education leaders.